Clinical and metabolic parameters, Ca2+, parathormone depending on serum 25(OH)D concentration in hypertensive patients in the West-Ukrainian population - Semianiv, Marianna; Sydorchuk, Larysa (Journal of Education, Health and Sport, 2021)
Introduction. Low plasma levels of 25-OH vitamin D (25(OH)D) have been associated with an increased prevalence of hypertension. The purpose of the research was to establish the association of clinical and metabolic parameters, Ca2+, parathormone and serum 25(OH)D concentration in hypertensive patients in the West-Ukrainian population. Material and method. 100 subjects with essential arterial hypertension (EAH) and target-organ damaging (2nd stage), moderate, high, very high cardiovascular risk were involved in the case-control study. Among them, 70,84% females, 29,16% males, mean age 57,86±7,81 yo. The control group consisted of 60 healthy individuals. All recruited patients were examined for heart rate, systolic and diastolic blood pressure (SBP, DBP); SCORE, BMI, waist and hip circumference (WC, HC); lipid panel, serum glucose and ionized calcium, 25(OH)D, parathormone levels were studied. Patients were divided into groups depending on total serum 25(OH)D concentration. Results. Low 25(OH)D concentration (<30 ng/ml) in patients with EAH was associated with arrhythmia, headache, sleep disturbance, weakness, fatigue, and increased total 10-year risk for fatal CVD SCORE>5,0%. We found higher SBP and DBP by 9,12% (р=0,014) and 5,17% (р=0,047), higher BMI in men and women – by 20-28,11% (р<0,05), as well as higher values of WC and HC by 8,69-11,92% (р<0,05) in hypertensive patients with hypovitaminosis D. In addition, obesity (BMI≥30,0 kg/m2), hyperglycemia, hypertriglyceridemia was more frequent – by 43% (p<0,05), 43,13% (p<0,001) and 59,37% (p=0,023), respectively. The level of ionized Ca2+ was slightly higher in healthy individuals (p=0,047) with low vitamin D concentration. PTH was compensatory increased by 31,85% (p=0,048) in hypertensive patients with hypovitaminosis D. Conclussions. Hypovitaminosis D is associated with more severe metabolic, hemodynamic disorders and clinical symptoms in hypertensive patients in the West-Ukrainian population.